THE STUDY OF LINGUISTIC ON MINAHASA ETHNIC VOCAL MUSIC - Sanger, Maikel B.G. (IJRDO- Journal of Educational Research, 2017)
Some research states that music is a language, both of which use sound media. Therhythm of language also allows the same rhythm of music for a particular culturelanguage. The Minahasa ethnic group has a diverse array of cultural traditions suchas language and culture. This ethnic has a series of language types with each accentor a distinctive intonation that is said to be unique. On the other hand, its distinctivesinging tradition is also very united with the people who live in it. If a typical accentis part of the Minahasa language language and the distinctive singing tradition is partof the Minahasa culture, can both be linked? Is the Minahasa way of singinginfluenced by the accent of the language? By looking at these problems, theresearcher wanted to give an idea of how the language relation by way of singing ofMinahasa people through the title of Linguistic Review on Minahasa Vocal Music.To answer the problem, the researcher uses the C. Dalhaus method of formalanalysis: explains the structure of a work in terms of function and relationshipbetween sections and elements, energetic interpretation: relates to the phase ofmovement or stretch of the tension, gestalt analysis: view the work as overall,hermeneutics: the interpretation of music in the context of an emotional statement oran external meaning. The research titled Linguistic Review of Minahasa EthnicVocal Music is a multi-disciplinary research because it will discuss two differentdisciplines of language discipline and music science. This research is categorized asdescriptive research because it will give description about how the elements oflanguage process in the way of singing people Minahasa.